Antioxidant and protective effect of Cynara cardunculus against paracetamol induced liver mitochondria oxidative stress. - Nacera BAALI; Zahia Belloum; Ahmed Menad; Souad Ameddah; Fadila Benayache; Samir Benayache (International Journal of Phytomedicine, 2014)
Cynara cardunculus L. (Asteraceae), commonly known as cardoon, is a Mediterranean species that grows naturally in harsh habitat conditions. It is used as a food for its nutritional value and ethnomedicinal properties linked to liver cleansing. The aim of the present study was to evaluate the hepatoprotective action of Cynara cardunculus butanolic extract (CCBE) against paracetamol (APAP) induced acute liver injury in rats. Results showed that APAP intoxication caused increase levels of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP). This phenomenon was paralleled by an impaired liver mitochondria redox status (reduced glutathione (GSH)), glutathione peroxidase (GPx), glutathione S-transferase (GST), and superoxide dismutase (SOD) and increased lipid peroxidation (LPO) in APAP treated rats. The pretreatment with CCBE blocked the increases of serum enzymes, reversed the mitochondrial LPO levels, and restored the mitochondrial antioxidant defense system (GSH, GST, GPX and SOD). The effect of CCBE was comparable to that of standard antioxidant N-acetylcysteine. Moreover, the antioxidant property of CCBE was also proved by in vitro assays as established by DPPH and hydroxyl radical scavenging activity and iron chelating ability. Our results indicate that the protective mechanism of CCBE may underlie the radical scavenging activity and the enhancement of mitochondrial antioxidant system.